Comparison of Structural Subscapularis Integrity After Latarjet Procedure Versus Iliac Crest Bone Graft Transfer. Issue 10 (9th October 2020) - Siegert, Paul; Plachel, Fabian; Akgün, Doruk; Baur, Alexander D.J.; Schulz, Eva; Auffarth, Alexander; Tauber, Mark; Moroder, Philipp
Background: Although clinical outcome scores are comparable after coracoid transfer procedure (Latarjet) and iliac crest bone graft transfer (ICBGT) for anterior shoulder instability with glenoid bone loss, a significant decrease in internal rotation capacity has been reported for the Latarjet procedure. Hypothesis: The subscapularis (SSC) musculotendinous integrity will be less compromised by ICBGT than by the Latarjet procedure. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively analyzed pre- and postoperative computed tomography (CT) scans at short-term follow-up of 52 patients (26 Latarjet, 26 ICBGT) previously assessed in a prospective randomized controlled trial. Measurements included the preoperative glenoid defect area and graft area protruding the glenoid rim at follow-up and tendon thickness assessed through SSC and infraspinatus (ISP) ratios. Fatty muscle infiltration was graded according to Goutallier, quantified with muscle attenuation in Hounsfield units, and additionally calculated as percentages. We measured 3 angles to describe rerouting of the SSC musculotendinous unit around the bone grafts. Results: SSC fatty muscle infiltration was 2.0% ± 2.2% in the Latarjet group versus 2.4% ± 2.2% in ICBGT ( P = .546) preoperatively and showed significantly higher values in the Latarjet group at follow-up (5.3% ± 4.5% vs 2.3% ± 1.7%; P = .001). In total, 4 patients (15.4%) in the Latarjet group showed a progression from grade 0 to grade 1 at follow-up, whereas no changes in the ICBGT group were noted. The measured rerouting angle of the SSC muscle was significantly increased in the Latarjet group (11.8° ± 2.1°) compared with ICBGT (7.5° ± 1.3°; P < .001) at follow-up, with a significant positive correlation between this angle and fatty muscle infiltration ( R = 0.447; P = .008). Ratios of SSC/ISP tendon thickness were 1.03 ± 0.3 in the Latarjet group versus 0.97 ± 0.3 ( P = .383) in ICBGT preoperatively and showed significantly lower ratios in the Latarjet group (0.7 ± 0.3 vs 1.0 ± 0.2; P < .001) at follow-up. Conclusion: Although clinical outcome scores after anterior shoulder stabilization with a Latarjet procedure and ICBGT are comparable, this study shows that the described decline in internal rotation capacity after Latarjet procedure has a radiographic structural correlate in terms of marked thinning and rerouting of the SSC tendon as well as slight fatty degeneration of the muscle.